Self-etching template method to synthesize hollow dodecahedral carbon capsules embedded with Ni–Co alloy for high-performance electromagnetic microwave absorption. (August 2020) - Qiu, Hongfang; Zhu, Xiaoyu; Chen, Ping; Liu, Jialiang; Zhu, Xiuling
Abstract: We employ self-etching template method to prepare an ideal electromagnetic wave (EMW) absorber, which is hollow dodecahedral carbon capsules embedded with Ni–Co alloy particles. The hollow dodecahedral polydopamine (PDA) capsules are constructed by the Ni(OH)2 /ZIF-67 template automatically etched off during in situ polymerization of Dopamine·HCl. N -doped carbon capsules (NCs) embedded with Ni–Co alloy particles (named as Air@NCs€Ni–Co) are obtained after the thermal treatment of Ni(OH)2 /ZIF-67@PDA. The EMW absorption performance of Air@NCs€Ni–Co has been tuned by different contents of Ni(OH)2 at 700 o C. The minimum reflection loss ( RL min ) value is −36.5 dB at 14.77 GHz with a thickness of 2.2 mm. The effective bandwidth ( RL < −10 dB) can reach up to 6.55 GHz (from 11.45 to 18 GHz) with a thickness of 2.3 mm, which covers the whole Ku band. Potentially, our study provides a new platform for subtly building hollow dodecahedral carbon capsules embedded with alloy particles using ZIF as self-etching template. Graphical abstract: Image 1 Highlights: The hollow dodecahedral carbon capsules Air@NCs€Ni-Co were obtained by novel method-self-etching template method. The special structure, interface between Air/Ni-Co, Air/NCs and Ni-Co/NCs, contribute to enhancing dielectric loss (interfacial polarization). The effective bandwidth can reach up to 6.55 GHz at a thickness of 2.3 mmRLmin value is –36.5 dB at 14.77 GHz with a thickness of 2.2 mm. It is completely meet with the characteristics of low thickness, wide band, light weight and strong absorption.